A New Methodology for Nonlinear Dynamic Analysis of Reinforced-Concrete Buildings Including Their Pile Foundations. Issue 1 (January 2014) - Lee, Kang Seok
At present, information on foundation–structure interactions of buildings is lacking. As a result, seismic performance evaluations of buildings seldom consider the effect of foundation performance on the building response. Recent destructive earthquakes, such as the Hokkaido Nansei-oki earthquake (magnitude M = 7.8, Japan, 1993), Northridge earthquake ( M = 6.7, U.S.A., 1994), Hyogoken-Nambu earthquake ( M = 7.2, Japan, 1995), Chi-Chi earthquake ( M = 7.6, Taiwan, 1999), Niigata Chuetsu earthquake ( M = 6.8, Japan, 2004), Sichuan earthquake ( M = 7.9, China, 2008), and Tohokuchiho Taiheiyo earthquake ( M = 9.0, Japan, 2011), have shown that building damage is significantly affected by the degree of damage sustained by the building foundation, and by the interaction between the building and its foundation. This paper presents a new methodology for nonlinear dynamic analysis of the seismic performance of reinforced-concrete (RC) buildings considering the pile foundation–structure interaction. The proposed method is applied to an actual example building that was severely damaged during the Hokkaido Nansei-oki earthquake. The results reveal that the method proposed in this study is able to predict the seismic performance of an RC building with a pile foundation and can provide fundamental data for the seismic design of such buildings.